Determinant factors of protective behaviors regarding erosion and coastal flooding risk. (July 2021) - Navarro, Oscar; Mambet, Constance; Barbaras, Clément; Chadenas, Céline; Robin, Marc; Chotard, Manon; Desvergne, Laura; Desse, Michel; Chauveau, Etienne; Fleury-Bahi, Ghozlane
Abstract: The increasing vulnerability of coastal areas to climate change and hazards has the authorities seeking the best way to protect the population. Because it is essential for citizens to contribute to their own protection, it is increasingly necessary to take their knowledge and perceptions into account. Two studies have been conducted to identify the factors that could explain protective behavior regarding coastal erosion and flooding risks: a qualitative study using interviews with 32 inhabitants of municipalities exposed to coastal risks, and a quantitative study using questionnaires with 237 participants exposed to coastal erosion (N = 116) and coastal flooding (N = 121). Thematic content and statistical analysis (multiple linear regression) have been used. The results indicate that flooding is considered a personal risk with heightened involvement, and thus necessitates personal action for self-protection. Erosion appears to be a collective risk, impacting all inhabitants, as well as being slower and easier to anticipate. The physical characteristics of the phenomenon will thus determine the dynamics and functioning of social knowledge on risk assessment and on the motivation to protect oneself.